Baclofen for the Treatment of Alcohol Use Disorder in Patients With Liver Cirrhosis: 10 Years After the First Evidence - Mosoni, Carolina; Dionisi, Tommaso; Vassallo, Gabriele Angelo; Mirijello, Antonio; Tarli, Claudia; Antonelli, Mariangela; Sestito, Luisa; Rando, Maria Margherita; Tosoni, Alberto; De Cosmo, Salvatore; Gasbarrini, Antonio; Addolorato, Giovanni (Frontiers in Psychiatry, 2018)
Alcohol Use Disorder (AUD) is a chronic and relapsing condition characterized by harmful alcohol intake and behavioural-cognitive changes. AUD is the most common cause of liver disease in the Western world. Alcohol abstinence is the cornerstone of therapy in alcoholic patients affected with liver disease. Medical recommendations, brief motivational interventions and psychosocial approach are essential pieces of the treatment for these patients; however, their efficacy alone may not be enough to achieve total alcohol abstinence. The addition of pharmacological treatment could improve clinical outcomes in AUD patients. Moreover, pharmacological treatments for AUD are limited in patients with advanced liver disease, since impaired liver function affects drugs metabolism and could increase the risk of drugs-related hepatotoxicity. At present, only baclofen has been tested in RCTs in patients with advanced liver disease. This medication was effective to reduce alcohol intake, to promote alcohol abstinence and to prevent relapse in AUD patients affected by liver cirrhosis. In addition, the drug showed a safe profile in these patients. In this review, clinical studies about efficacy and safety of baclofen administration in patients with AUD and advanced liver disease will be reviewed. Open question about the most appropriate dose of the drug, duration of the treatment and need of additional studies will also be discussed.